The influence of demographic factors on the supply of company training places in Germany - Maier, Tobias [Verfasser]; Walden, Günter [Verfasser] (My University, 2014)
"In the German dual system of vocational education and training, the question arises of whether and how enterprises react to demographic changes by adjusting their supply of training places. We conduct a time series on Western German data from 1970 to 2011 and construct a panel data set from 1977 to 2011 based on data of the West German states ('Bundesländer') to estimate the influence of demographic changes over time. We can show that demographic factors strongly influenced the Federal Republic prior to 1990. After the reunification, a positive influence of demographic factors is still observed but only for young people with higher levels of education; in large part, factors related to economic growth and the job market dominate. Our findings suggest that, compared to prior times, policy makers nowadays only have limited abilities to influence the number of training places offered by companies through appeals to community spirit. Instead, strategies of gaining additional training places should be geared towards the economic interests of enterprises." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; G 1.1.1 Demografie; Ausbildungsplatzangebot; Ausbildungsbeteiligung; Einflussfaktor; Demografische Faktoren; Historische Entwicklung; Quantitative Angaben; 1970-2011